2020
DOI: 10.1515/jpem-2020-0339
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes distress in Indian children with type 1 diabetes mellitus and their mothers

Abstract: BackgroundChildren and their mothers, who are usually the primary caregivers, are likely to be distressed due to type 1 diabetes (T1DM).Objectives(1) To assess diabetes-specific distress (DD) perceived by children and adolescents with T1DM and their mothers and association of distress between children and mothers. (2) To study the association of diabetes distress with glycemic control and disease duration.SubjectsChildren and adolescents with T1DM over eight years and their mothers.MethodsClinical data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…Our study demonstrated a high proportion of children, adolescents and carers experience diabetes distress, consistent with previous studies 8,10,15,16,18 . The mean percentage scores in our study ranged from 32 for children, to 44 for parents‐of‐adolescents, with a maximum possible percentage score being 100 (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study demonstrated a high proportion of children, adolescents and carers experience diabetes distress, consistent with previous studies 8,10,15,16,18 . The mean percentage scores in our study ranged from 32 for children, to 44 for parents‐of‐adolescents, with a maximum possible percentage score being 100 (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…However, other similar, though not identical, PAID questionnaires have used various thresholds between 34 and 50/100 to identify 'severe distress'. 8,15,16,[18][19][20] The mean distress scores reported by our cohort suggest that a large portion are experiencing moderate to severe diabetes distress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations